PENGUJIAN ZAT WARNA DARI EKSTRAK BUAH NAGA (HYLOCEREUS POLYRHIZUS) DAN CENGKODOK (MELASTOMAS MALABATHRICUM) SEBAGAI INDIKATOR ALAMI - Tuti Kurniati (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACT The purpose of this research was to test the dye on extracts of dragon fruit (Hylocereus polyrhizus) and cengkodok (Melastoma malabathricum) as a natural indicator. This natural indicator was made by utilizing the content of the dye (anthocyanin) in plants which have fruit or flowers. Maseration was conducted by using two solvents consist of aquadest and ethanol to determine which one of the best solvent. Aquadest solvent showed as the best extractor for dragon fruit. Meanwhile ethanol solvent as the best extractor for cengkodok (70%). The best composition of the dragon fruit and cengkodok was 1:1 of solvent meanth 1 gram of dragon fruit or cengkodok was dissolved in 1 ml of solvent. The best soaking time of dragon fruit and cengkodok was 90 minutes. Test the pH range in a solution of pH 1-14 for dragon fruit gave pH from 1 to 4 as a pH indicator stretch natural, and for cengkodok gave pH from 11 to 14 as a pH indicator stretch natural.Keywords: cengkodok, dragon fruit, natural indicator, pH range